Implementing The Task-based Learning Approach In Teaching Linguistics To First Year University Students - Nesrine Aoudjit Bessai (Al-Lisaniyyat, 2015)
Communicative language teaching has given birth to a number of approaches that share the same basic principles, but which spell out different instructional principles. These approaches include Content-Based Instruction (CBI) and Task-Based Learning (TBL). They are based on the premises that language learning is a cognitive process where the learner is viewed as an active participant in the learning process and the teacher as a facilitator and monitor. Bearing in mind these principles when teaching the module of Linguistics, we have tried to design a linguistics lesson following the task-based approach, in which we integrate the teaching of linguistic content and language.